Math Problem Statement

Buktikan soal ini

Buktikan soal ini

Solution

The image you provided contains three matrix properties that can be proven using matrix algebra rules. I will go step by step to prove each one:

1. Proof of (AT)1=(A1)T\left( A^T \right)^{-1} = \left( A^{-1} \right)^T

This property states that the inverse of the transpose of a matrix is equal to the transpose of the inverse of the matrix.

Proof:

  • Let AA be an invertible matrix.

  • The inverse of a matrix AA is defined as the matrix A1A^{-1} such that: AA1=A1A=IA A^{-1} = A^{-1} A = I where II is the identity matrix.

  • Taking the transpose of both sides of AA1=IA A^{-1} = I, we get: (AA1)T=IT=I\left( A A^{-1} \right)^T = I^T = I

  • By the property of transposes, (AB)T=BTAT\left( A B \right)^T = B^T A^T, so: (AA1)T=(A1)TAT=I\left( A A^{-1} \right)^T = \left( A^{-1} \right)^T A^T = I This shows that (A1)T\left( A^{-1} \right)^T is the inverse of ATA^T.

Therefore, (AT)1=(A1)T\left( A^T \right)^{-1} = \left( A^{-1} \right)^T

2. Proof of (A1)1=A\left( A^{-1} \right)^{-1} = A

This property states that the inverse of the inverse of a matrix is the matrix itself.

Proof:

  • By the definition of an inverse, if A1A^{-1} is the inverse of AA, then: AA1=A1A=IA A^{-1} = A^{-1} A = I
  • To find (A1)1\left( A^{-1} \right)^{-1}, we need to find the matrix that, when multiplied by A1A^{-1}, gives the identity matrix: A1(A1)1=IA^{-1} \left( A^{-1} \right)^{-1} = I From this, we can conclude that (A1)1=A\left( A^{-1} \right)^{-1} = A.

Therefore, (A1)1=A\left( A^{-1} \right)^{-1} = A

3. Proof of (ABC)1=C1B1A1\left( ABC \right)^{-1} = C^{-1} B^{-1} A^{-1}

This property states that the inverse of the product of matrices is the product of their inverses in reverse order.

Proof:

  • Let AA, BB, and CC be invertible matrices.
  • We need to show that: (ABC)(C1B1A1)=I\left( ABC \right) \left( C^{-1} B^{-1} A^{-1} \right) = I
  • Using the associative property of matrix multiplication, we calculate: (ABC)(C1B1A1)=A(B(CC1)B1)A1\left( ABC \right) \left( C^{-1} B^{-1} A^{-1} \right) = A \left( B \left( C C^{-1} \right) B^{-1} \right) A^{-1} Since CC1=IC C^{-1} = I and BB1=IB B^{-1} = I, this simplifies to: A(II)A1=AA1=IA \left( I I \right) A^{-1} = A A^{-1} = I Thus, (ABC)1=C1B1A1\left( ABC \right)^{-1} = C^{-1} B^{-1} A^{-1}.

Therefore, (ABC)1=C1B1A1\left( ABC \right)^{-1} = C^{-1} B^{-1} A^{-1}

Summary

We have successfully proven all three properties:

  1. (AT)1=(A1)T\left( A^T \right)^{-1} = \left( A^{-1} \right)^T
  2. (A1)1=A\left( A^{-1} \right)^{-1} = A
  3. (ABC)1=C1B1A1\left( ABC \right)^{-1} = C^{-1} B^{-1} A^{-1}

Let me know if you'd like further explanations or additional examples.


Relative Questions:

  1. What are the conditions for a matrix to be invertible?
  2. Can you extend the property of matrix product inverses to more than three matrices?
  3. How does the determinant of a matrix relate to its invertibility?
  4. What is the difference between a matrix transpose and its inverse?
  5. Can a non-square matrix have an inverse?

Tip:

For any matrix AA, A1A^{-1} exists if and only if AA is square and its determinant is non-zero.

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Matrix Algebra
Inverse Matrices
Transpose of Matrices

Formulas

(A^T)^{-1} = (A^{-1})^T
(A^{-1})^{-1} = A
(ABC)^{-1} = C^{-1}B^{-1}A^{-1}

Theorems

Inverse of the transpose theorem
Inverse property theorem
Inverse of matrix multiplication theorem

Suitable Grade Level

Undergraduate/Graduate level